9 - Démocratisation, exacerbation, régime identitaire et rivalités ethniques: Le cas du Sud-Cameroun: 10.4314/ad.v27i1.22157 - Zambo , Belinga Joseph-Marie (Africa Development, 2002)
The socio-ethnic composition of Cameroon (stating the obvious) is basica marked by the seal of plural identities. This plurality entails some ambivalence. Wher its inherent cultural enrichment may be viewed as a means of building a virtual plu nation, such plurality can equally and on the contrary secrete the major bifurcations th could hamper the attainment of such a goal. The ethnic idiosyncrasies revisited since t re-institution of political pluralism in December 1990, thanks to the initiative of t identity promoters who adopted it as their preferred modus operandi, are actually workin to make fissures into the waterproof edifice of a national entity. This paper examines expression of the exacerbation of such an identity within two ethnic groups in the Sou of the country and the ensuing conflicts that occurred during the country's politi watershed culminating in the October 1992 presidential election.